2017
DOI: 10.1126/sciimmunol.aan5393
|View full text |Cite
|
Sign up to set email alerts
|

Recovery from the Middle East respiratory syndrome is associated with antibody and T cell responses

Abstract: The Middle East Respiratory Syndrome-coronavirus (MERS-CoV) causes a highly lethal pneumonia. MERS was recently identified as a candidate for vaccine development but most efforts focus on antibody responses, which are often transient after CoV infections. CoV-specific T cells are generally long-lived but the virus-specific T cell response has not been addressed in MERS patients. Here, we obtained PBMCs and/or sera from 21 MERS survivors. We detected MERS-CoV-specific CD4 and CD8 T cell responses in all MERS su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
265
2
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 270 publications
(287 citation statements)
references
References 34 publications
18
265
2
2
Order By: Relevance
“…49,57 Studies of MERS survivors showed that MERS-CoV-specific antibody responses tended to be lower and transient in patients with mild or subclinical disease when compared with patients with severe disease, in whom MERS-CoV-specific antibody responses were detected for at least 2 years. [57][58][59][60] In contrast, T-cell responses were detected in all MERS survivors for at least 2 years. 59 The transitory nature of the antibody response in mild disease and greater stability of the T-cell response suggest that induction of both will be required for optimal longterm protection; the measurement of both will enhance the accuracy of prevalence studies.…”
Section: Protective and Deleterious Immune Responsesmentioning
confidence: 90%
See 1 more Smart Citation
“…49,57 Studies of MERS survivors showed that MERS-CoV-specific antibody responses tended to be lower and transient in patients with mild or subclinical disease when compared with patients with severe disease, in whom MERS-CoV-specific antibody responses were detected for at least 2 years. [57][58][59][60] In contrast, T-cell responses were detected in all MERS survivors for at least 2 years. 59 The transitory nature of the antibody response in mild disease and greater stability of the T-cell response suggest that induction of both will be required for optimal longterm protection; the measurement of both will enhance the accuracy of prevalence studies.…”
Section: Protective and Deleterious Immune Responsesmentioning
confidence: 90%
“…[57][58][59][60] In contrast, T-cell responses were detected in all MERS survivors for at least 2 years. 59 The transitory nature of the antibody response in mild disease and greater stability of the T-cell response suggest that induction of both will be required for optimal longterm protection; the measurement of both will enhance the accuracy of prevalence studies.…”
Section: Protective and Deleterious Immune Responsesmentioning
confidence: 90%
“…A recent study analyzing patients who survived MERS virus infection demonstrated that survival depended on induction of both a cell-mediated immune response and neutralizing antibody [36]. The analysis showed a correlation between the severity of symptoms, the activation of T cells extracted from peripheral blood mononuclear cells, and the intensity of the antibody response.…”
Section: Discussionmentioning
confidence: 99%
“…First, the study was based on chart reviews, and findings should be interpreted with caution. Second, we did not collect information on the type of antiviral treatment or other supportive treatments given after diagnosis which may have affected clinical outcomes . Third, despite this being the first investigation in this population, including a number of potential predictors for recovery delay, additional relevant predictors should be explored, such as the level of camel exposure, for example, hospital‐acquired infections.…”
Section: Discussionmentioning
confidence: 99%